Metode Nilai Jual Relatif Sebagai Dasar Penentuan Harga Pokok Produk Bersama - Megawati Megawati; Maryani Maryani; Rusmianto Rusmianto (Jurnal Ilmiah ESAI, 2018)
The objective of this study is to know: (1) the influence of BPD Knowledge on budgets onvillage financial oversight (APBDesa); (2) the influence of interaction of Communityparticipation on the relationship between knowledge of BPD on budget and village financialoversight (APBDesa); (3) The Influence of Public Policy Transparency Interaction on therelationship between knowledge of BPD on budgets and village financial oversight (APBDesa)and (4) Influence of BPD Knowledge interaction on budget, community participation, andtransparency of public policy towards village financial oversight (APBDesa). This research wasconducted by using the members of the Village Consultative Board (BPD) villages in WaysulanSub-district, South Lampung Regency (8 Villages) as its object. The hypothesis in this researchwas tested by using multiple analysis (multiple regression). The data processing is done withthe help of SPSS statistical application. Hypothesis testing performed after multiple regressionmodels are used free of violation of classical assumptions, so that the test results can beinterpreted appropriately. The conclusions can be drawn is that the knowledge of villageconsultative bodies (BPD) has a significant positive effect on the level of village financialoversight, while public participation, accountability, and transparency of public policy do notaffect the relationship between the knowledge of members of village consultative bodies (BPD)these three variables (public participation, accountability, and transparency of public policy)directly affect the level of oversight of village financial management